Does country governance foster revenue efficiency of Islamic and conventional banks in GCC countries? - Kamarudin, Fakarudin; Sufian, Fadzlan; Md Nasir, Annuar (Emerald Group Publishing Limited, 2016)
Purpose The purpose of this paper is to provide new empirical evidence on the impact of country governance on the revenue efficiency of Islamic and conventional banks. The empirical analysis is confined to Islamic and conventional banks operating in the Gulf Cooperation Council (GCC) countries banking sectors during the period of 2007-2011.